solve for x-1/x-2 + x-3/x-4 =10/3
Answers
Answered by
1
Taking the LCM (x-2)(x-3)3
we will get
3(x-4) (x-1) + 3(x-2)(x-3) = 10 (x-2)(x-4)
3( x² -5x +1) + 3(x²-5x+6) = 10 (x²- 6x +8)
3x²−15x+3+3x²−15x+18=10x²−60x+80
0=4x²−30x+59\
solving through quadratic formula
we get x= 30 +- √900 - 944/ 8
we will get
3(x-4) (x-1) + 3(x-2)(x-3) = 10 (x-2)(x-4)
3( x² -5x +1) + 3(x²-5x+6) = 10 (x²- 6x +8)
3x²−15x+3+3x²−15x+18=10x²−60x+80
0=4x²−30x+59\
solving through quadratic formula
we get x= 30 +- √900 - 944/ 8
Similar questions